Effect of spermidine on ameliorating spermatogenic disorders in diabetic mice via regulating glycolysis pathway - Jin-Yuan Wang; Duo Ma; Min Luo; Yong-Peng Tan; Ou Zhong; Ge Tian; Yong-Ting Lv; Mei-Xiang Li; Xi Chen; Zhi-Han Tang; Lin-Lin Hu; Xiao-Can Lei (BMC, 2022)
Abstract Diabetes mellitus (DM), a high incidence metabolic disease, is related to the impairment of male spermatogenic function. Spermidine (SPM), one of the biogenic amines, was identified from human seminal plasma and believed to have multiple pharmacological functions. However, there exists little evidence that reported SPM's effects on moderating diabetic male spermatogenic function. Thus, the objective of this study was to investigate the SPM's protective effects on testicular spermatogenic function in streptozotocin (STZ)-induced type 1 diabetic mice. Therefore, 40 mature male C57BL/6 J mice were divided into four main groups: the control group (n = 10), the diabetic group (n = 10), the 2.5 mg/kg SPM-treated diabetic group (n = 10) and the 5 mg/kg SPM-treated diabetic group (n = 10), which was given intraperitoneally for 8 weeks. The type 1 diabetic mice model was established by a single intraperitoneal injection of STZ 120 mg/kg. The results showed that, compare to the control group, the body and testis weight, as well the number of sperm were decreased, while the rate of sperm malformation was significantly increased in STZ-induced diabetic mice. Then the testicular morphology was observed, which showed that seminiferous tubule of testis were arranged in mess, the area and diameter of which was decreased, along with downregulated anti-apoptotic factor (Bcl-2) expression, and upregulated pro-apoptotic factor (Bax) expression in the testes. Furthermore, testicular genetic expression levels of Sertoli cells (SCs) markers (WT1, GATA4 and Vimentin) detected that the pathological changes aggravated observably, such as the severity of tubule degeneration increased. Compared to the saline-treated DM mice, SPM treatment markedly improved testicular function, with an increment in the body and testis weight as well as sperm count. Pro-apoptotic factor (Bax) was down-regulated expression with the up-regulated expression of Bcl-2 and suppression of apoptosis in the testes. What's more, expression of WT1, GATA4, Vimentin and the expressions of glycolytic rate-limiting enzyme genes (HK2, PKM2, LDHA) in diabetic testes were also upregulated by SPM supplement. The evidence derived from this study indicated that the SMP's positive effect on moderating spermatogenic disorder in T1DM mice's testis. This positive effect is delivered via promoting spermatogenic cell proliferation and participating in the glycolytic pathway's activation.